2021
DOI: 10.1038/s41467-020-20398-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cascades on burstiness-controlled temporal networks

Abstract: Burstiness, the tendency of interaction events to be heterogeneously distributed in time, is critical to information diffusion in physical and social systems. However, an analytical framework capturing the effect of burstiness on generic dynamics is lacking. Here we develop a master equation formalism to study cascades on temporal networks with burstiness modelled by renewal processes. Supported by numerical and data-driven simulations, we describe the interplay between heterogeneous temporal interactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…For the temporal network, an essential factor is the network memory [38,[40][41][42], which means that edges that existed in the current time step may already occur in previous time steps. Sun et al [43] revealed that network memory inhibits the spreading process for SIR models, in which the epidemic threshold is enlarged while the spreading size decreases.…”
Section: Introductionmentioning
confidence: 99%
“…For the temporal network, an essential factor is the network memory [38,[40][41][42], which means that edges that existed in the current time step may already occur in previous time steps. Sun et al [43] revealed that network memory inhibits the spreading process for SIR models, in which the epidemic threshold is enlarged while the spreading size decreases.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of algorithmic bias has been recently modeled in an array of concrete scenarios [18,22,25], a general theoretical framework systematically linking social dynamics, network structure and algorithmic filtering has been missing so far. Here we have put forward such a formalism by extending previous work on binary-state dynamics [2,24,29,[34][35][36]45] with a notion of bias and applying it to synthetic and real-world social networks. While our formalism applies to any binary-state dynamics, we have showcased its flexibility by focusing on the noisy voter, language, and majority-vote models, which consider a (pairwise or group-based) copying or herding mechanism, alongside random or idiosyncratic changes of opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Our formalism provides a flexible way to parametrize a combination of algorithmic filters and mechanisms of social interactions in terms of transition rates. As such, it may help identify the features of algorithms that promote dynamical and structural polarization in online platforms arguably driven by a mixture of social processes, from homophily [26,27] to social contagion [28,29]. This will require a validation of our theoretical framework by either fitting observational data with specific models, using automatic model selection [56,57] and statistical inference techniques [58], or uncovering causal relationships with controlled experiments of online social behavior [59,60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations